Applying antitrust in digital markets: Foundations and approaches - Mark Jamison (American Enterprise Institute (AEI), 2019)
This paper analyzes conflicts that arise when trying to apply traditional antitrust principles in the context of digital markets.
Keywords: A; 330; Antitrust; Department of Justice DOJ; Federal Trade Commission FTC